Investigation of prospective mathematics teachers' knowledge of assessment in the context of summative and formative assessment - AKKOÇ, HATİCE (My University, 2011)
Recent research demonstrates that formative assessment can significantly contribute to learning but generally is not used by teachers. The aim of this study is to investigate the development of prospective teachers with regard to assessment. 40 prospective mathematics teachers are involved in the study. Workshops were conducted aiming at developing pedagogical content knowledge. A survey was given to 40 prospective mathematics teachers before and after the workshops to find out whether there was a difference in their pedagogical knowledge. The data were analyzed qualitatively. Results indicated significant improvements in prospective teachers\" knowledge of assessment especially of formative assessment. Before the workshops, candidates used assessment for summative purposes whereas they used assessment formatively after first workshop. After the second workshop they started to use both summative and formative assessment in accordance with their purposes. It was observed that there is significant enrichment (70%) in the candidates\" conceptual understanding of assessment.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Social Sciences and Humanities; Sociology; Education; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); EDUCATION & EDUCATIONAL RESEARCH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; Social Sciences & Humanities; Formative assessment; summative assessment; teacher education; pedagogical content knowledge